The Influence Of Strategic Planning, Strategic Implementation With Stakeholders Support On The Performance Of Regional Drinking Water Companies In Region II - Purwatiningsih, Purwatiningsih (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2024)
The purpose of this study is to analyze the influence of strategic planning on company performance. To analyze the influence of strategic planning on strategy implementation. To analyze the influence of stakeholder support on strategy implementation. To analyze the influence of strategy implementation on company performance. This research is a quantitative research, with a survey approach. Through the survey, not all individuals are observed but only take samples from the population. The location of this research is PDAM Region II. The sample in this study was 100 respondents using cluster random sampling method. Data analysis method and hypothesis testing with Structural Equation Model (SEM). In testing the model using SEM, there are seven steps that must be taken.  Results of the analysis as follows: the value of strategic planning variables on the performance of companies with a p-value less than the lowest average. Variable value of strategic planning to the implementation of the strategy has a p-value less than the lowest average value. The value of the variable support of stakeholders on the implementation of the strategy with p-value less than the lowest average. The value of the variable implementation of the strategy on the performance of companies with a p-value less than the value of the lowest average. From the analysis, it can be concluded strategic planning affect the company's performance, strategic planning affect the implementation of the strategy, the support of influential stakeholders towards the implementation of the strategy and implementation of strategies affect the company's performance.